Pastoral nomadism in the archaeology of India and Pakistan - Leshnik, Lawrence S. (World archaeology, 1972)
Pastoral nomads have always figured importantly in the history of South Asia but their role has seldom been given serious anthropological attention. After a brief discussion of some general aspects of pastoral nomadism that have particular relevance for the archaeologist, three problems in the archaeology of India are considered. Although unrelated, each problem in its way admits of a pastoral nomad interpretation. The first is the familiar one of the Aryans, who, it is suggested, are likely initially to have used the products of indigenous craftsmen and for this very reason their identification has proven so elusive. The next section seeks to identify certain microlith-users whose connection with domestic animals is assured, with a nomadic adaptation recognizable in the last centuries B.C. The final section discusses the character of an important South Indian grave complex. Its specific Iranian traits and an artefactual assemblage in which horse equipment and weapons are prominent, again seem best explained by reference to the movements of pastoral nomads.